Analyzing the Perspectives of Instructors of General Medical Modules on the Inclusion of Health Humanities Fundamentals in the Curriculum - SeyedAmir Mohseni; Fattaneh Amuei; Siavash Moradi (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Medical/Health Humanities is considered a new field of study. This concept is looking for an answer to the question of how to make medical education, medical processes, and practice more humane so that the human aspects are respected more. In this research, we want to identify and explain the necessity and how to apply the essentials of medical humanities in the MD curriculum of Mazandaran University of Medical Sciences Materials and methods: The current research was qualitative and content analysis type research. The samples of this research were selected purposefully. The samples included university faculty members who had innovative educational processes and general course lecturers, or experts in medical education. Data collection continued until the collected data duplicated the previous data and data saturation occurred. Semi-structured group interview with a focus group discussion method was used for data collection and conventional content analysis method was used for data analysis. Results: After merging the codes extracted from the focus group discussion, classifying the codes, and repeated revisions 155 codes were identified. These codes were categorized into 14 categories, which were finally placed in two more general themes of “necessity” and “how”. In the theme of “necessity”, 6 categories and 60 codes were identified, including medical paradigms, Iranian medical tradition, issues in current medicine, medical technology, benefits of health/medical humanities education, and problems in the curriculum. In the “how” theme, 8 categories and 95 codes were identified, including applying for new courses, changing current courses, new topics, setting goals to strengthen skills, arts and humanities, education in practice, policy-making, and challenges. Conclusion: The result of this research showed that it is necessary to include the content of medical/health humanities in the general medical curriculum. Needs assessment in the definition of new courses and topics and the application of existing courses in the curriculum should be done to improve the quality of medical education. The inclusion of humanities content in the curriculum has challenges, such as cultural issues, resistance to change, medical hegemony, the presence of a clinical-oriented and reductionist point of view, the absence of an approved curriculum, and an overcrowded curriculum.